27+6x=3x-18

Simple and best practice solution for 27+6x=3x-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27+6x=3x-18 equation:


Simplifying
27 + 6x = 3x + -18

Reorder the terms:
27 + 6x = -18 + 3x

Solving
27 + 6x = -18 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
27 + 6x + -3x = -18 + 3x + -3x

Combine like terms: 6x + -3x = 3x
27 + 3x = -18 + 3x + -3x

Combine like terms: 3x + -3x = 0
27 + 3x = -18 + 0
27 + 3x = -18

Add '-27' to each side of the equation.
27 + -27 + 3x = -18 + -27

Combine like terms: 27 + -27 = 0
0 + 3x = -18 + -27
3x = -18 + -27

Combine like terms: -18 + -27 = -45
3x = -45

Divide each side by '3'.
x = -15

Simplifying
x = -15

See similar equations:

| .81x+.33=.42-.18x+.42 | | 11-9x=34-16x | | 17-2y=1 | | -171-9x=34-16x | | .6x-.53x=5 | | 10x-29=81 | | 0.6(d+3)=3d | | 71-2x=2x+19 | | 21q-40=16 | | c^4-9c^2+14=0 | | 6x+4x+3+6=3x+3+6x | | 4=7x-9 | | x=-4(2)-8 | | x=-4(1)-8 | | x=-4(0)-8 | | x=-4(-1)-8 | | x=-4(-2)-8 | | 4x+6=2x-3 | | 463a+34=3 | | x=4(2)-6 | | -25a^6+10a^5+45a^4=0 | | x=4(1)-6 | | x=4(0)-6 | | 170500=31000x | | x=4(-1)-6 | | x=4(-2)-6 | | 9m-11=-10-12m | | 0=-9x+8 | | 9x-23=67 | | 5(4x-2)=-10(-2x+1) | | y=4(-2)-6 | | 183-4x=32x+23 |

Equations solver categories